Manajemen Kolaboratif Dalam Penanggulangan Bencana Daerah Di Kabupaten Banjarnegara - Herlina Wahyu Tri Widyaningsih (Program Magister Administrasi Publik, Fakultas Ilmu Sosial dan Politik, Universitas Jenderal Soedirman, 2020)
Disaster measurement in Indonesia include in Banjarnegara District by collaborative management, which expected could solvable. The implementation of collaborative management of manajement disater in Banjarnegara District had human resources, budget, and equipment limitation. This situation been interesting researchers to exam the collaborative management of disaster management in Banjarnegara District. This research aims to analyze how collaborative management in disaster management at Banjarnegara District at response, recovery and developing phase, and to analyze the supporting and inhibiting factors to collaborative management of disaster management in Banjarnegara District and the strategies to solving the problem. This research was qualitative research with descriptive approach. Researh methode was case study. The informants select by purposive sampling techniques with consideration that informant realy understand about collaborative management of disaster management in Banjarnegara District, so could gave many information about research problems. The prime informants were the Head of BPBD, the Head of BPBD Operational Section, the Health Service, Secretary of government Banjarnegara District, Commission D of Regional Representative Council in Banjarnegara, and Head of Social Service. Supporting informant is the head of community organization. Data collection by interviews, observation and documentation. Research data were analyzed by interactive model. The results of this research been concluted: 1) Collaborative management of disaster management in Banjarnegara District over all not satisfaction comunity and not effective and efficient yet. At response phase could been doing quite well, at recovery phase could been doing well, and at developing phase could been doing well too but not finished at all yet caused by comunity land acquisition problem. BPBD could collaborate with some elements of government institution and non-governmental institutions in order to achieve a common goal which is to minimize the number of victims and the risk of disaster impacts, 2) Supporting factors were communication, commitment and mutual understanding among the stakeholders which be realized in collaboration and awareness all elements about their duties and responsibility so the limitation factors like human resources, equipment and budget can be solving by those collaboration. So that could say if collaborative management of disaster management in Banjarnegara District was solvable for disaster management in Banjarnegara District which has susceptible and disaster potenstions from several aspects, that was geographical, climatological, geological, and demographic social.